Essentials of Grant Writing in Medical Research: Opportunities and Challenges - Sharma, Mohan Raj (Nepalese Journal of Ophthalmology, 2024)
Introduction: Grant writing is a crucial skill for researchers seeking financial support for their projects. It involves crafting a compelling proposal demonstrating a project’s value, feasibility, and societal relevance. Objective: This paper aims to provide an overview of grant writing, including types of grants, steps in application, and strategies for effectively presenting research ideas. Also, challenges and solutions for successful grant proposal writing, emphasising the importance of structured planning and effective data visualisation techniques are presented. Methodology: Using Nepal’s research funding scenario as a backdrop, this manuscript is based on the articles published in the peer-reviewed literature, and the author’s experience of working as a grant reviewer for several organisations for over a decade. Practical examples and insights into the nuances of grant writing are included to guide researchers, particularly in resource-constrained settings like Nepal. Result: Information about grant and grant writing, funding organisations, their mode of awarding grants, steps of writing grant proposals, and dos and don’ts of grant proposals are elaborated in this review. Conclusion: Crafting an effective grant proposal is an iterative process that can be developed through practise and persistence. Familiarity with research methodologies, combined with guidance from an experienced mentor, plays a crucial role in successfully writing and securing funding for research projects.